Pengaruh Diferensiasi dan Inovasi Terhadap Kepuasan Pelanggan Dengan Keunggulan Bersaing Sebagai Variabel Intervening - Puspita Lianti Putri (Sekolah Pascasarjana Perbanas Jakarta, 2020)
This research aims to analyse competitive advantage as an intervening variable on Go-Pay customer satisfaction in Tebet, South Jakarta. This study uses differentiation and innovation strategies as independent variables, customer satisfaction as the dependent variable, and competitive advantage as an intervening variable. The number of samples in this study amounted to 150 respondents who were determined using the non-probability sampling method, simple random sampling. This research uses quantitative causal research, Go-Pay users as a sample. The data analysis method used in this study is the SEM (Structural Equation Modelling) model with the Analysis of Moment Structure (AMOS) program. The results showed that differentiation and innovation have a positive and significant effect on competitive advantage. Differentiation has a positive but not significant effect on customer satisfaction. Then, innovation has a positive and insignificant effect on customer satisfaction, and competitive advantage has a positive effect and significant on customer satisfaction. Competitive advantage as an intervening variable has a positive and significant effect on customer satisfaction. Competitive advantage as an intervening variable has a positive and significant effect on innovation and customer satisfaction.